Mengenal Konsep Dasar Soft News - Erwan Efendi; Sarmila Haerani Siregar; Arofah Sri Mulyani; Aghna Zainina (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to recognize soft news. This type of research is library research. The data obtained from the results of the author's references are obtained in various books and journals which are processed and analyzed based on the results of the references obtained, then developed with the imagination of the author in order to produce a goal of this writing. The results of this study contain soft news, where soft news is soft news or soft news, because news that is in the soft news category does not have to be broadcast immediately. By being able to get to know soft news, we can get more information even though some of it is just public opinion.